Designing Multimedia-based Presentation in Academic Speaking Classroom: Students' Strategies - Denty Marga Sukma; Joko Nurkamto; Nur Arifah Drajati (International Journal of Language Teaching and Education, 2018)
Educational technology is substantially aimed at assisting the teaching and learning process especially in material delivery that can be done using Powerpoint Presentation. Particularly, the integration of text-based material and a variety of media promote the likelihood that the audience experiences the effective information processing. Therefore, multimedia-based presentation that is accompanied by verbal explanation must be designed as effective as possible in order to foster the audience’s understanding. The current research was aimed at investigating the strategies employed by the students in designing multimedia-based presentation in Academic Speaking classroom. This qualitative research was carried out using case study approach to obtain the in-depth information. The data were collected through observation, document analysis, and interview. The results show that the students strategies in designing multimedia-based presentation are mainly to foster the audience’s thinking process. Those strategies are using heading to lead to thesis, using bullet list to create sequential delivery, and using the additional element to engage the audience. To make the slide gets into the logical manner, a transitional device is also required. This research will contribute to the teaching and learning process that uses presentation as the method of material delivery. The teacher and the student are expected to know the strategies to design an effective presentation that can promote the audience’s way to process the information. Keyword: academic speaking, educational technology, information processing, material delivery, multimedia-based presentation